IDENTIFIKASI PENYEBAB RISIKO KECELAKAAN KERJA PADA KEGIATAN KONSTRUKSI BANGUNAN GEDUNG DI DKI JAKARTA - Simanjuntak, Manlian Ronald. A.; Praditya, Rendy (Sam Ratulangi University, 2012)
The construction industry is one of the industrial sectors with high rates of workplace accidents. With respect to numbers of workplace accidents occurred is attributed frequently to the human error factor. To analyze workplace accidents occurred in building construction work that is caused byhuman error, therefore an approach is needed. The purpose of this research is to identify the factors that cause the human error risk which can lead to workplace accident in building construction work in DKI Jakarta. This study utilizes system approach principle. The mechanism describes relations among worker and organizational, managerial, as well as environment that explained the occurrence workplace accidents, directly or indirectly. This research is divided into two phases; the first phase identifies the frequent risk occurred in building construction work, whereas, the second phase identifies the cause of the occurrence risk. This research concluded that organizational and managerial factors are also considered to creating â€œholeâ€ in the workplace safety defense system. Therefore, an ideal system that involved all related parties is essential to prevent the workplace accidents.Keywords: Workplace accident, human error, risk, building construction